Exploring the EFL Iraqi students' competence in using and understanding idiomatic expressions - Hassan Jasim, Ban (International Journal of Psychosocial Rehabilitation, 2020)
For many language learners, especially those of Arabic origin, the most difficult part in learning idiomatic expression is learning both literal and figurative meanings of these idioms. idiom is a multi-word expression which has a meaning different from the sum of the meanings of the words it contains (e.g. Allan 1986, 237, Cruse 1986, 37, Chaika 1982, 200) This study aims at: 1. explaining the idiomatic expressions and clarifying the different types of methods and strategies of English idioms learning that EFL learners used to conclude the meaning of idiomatic expressions. 2. Identifying the Iraqi EFL university students' performance to recognize idioms to help them know the effective use of them. 3. Analyzing the causes of errors made by Iraqi EFL university students in using and understanding the idiomatic expressions. 4: Finding out the learners' errors in using idioms and pointing out whether there are any significant differences between the whole samples' performance. To fully fill the aims, a sample was chosen from the third-year students at the Department of English (College of Education for Humanities/University of Thi-Qar) during the academic year 2020-2021. The sample size is 50 students. The researcher makes sure of the variation that could affect the results. All the subjects of the sample are approximately the same age and have the same linguistic background. The researcher designed an idiom familiarity test to identify the problematic area in using and understanding idiomatic expressions and concluding the meaning of these idioms. The data were analyzed using descriptive statistics (frequency, mean score, and standard deviation) and inferential statistics (independent sample t-test). The whole results reveal that students exhibit a weak performance in the idioms familiarity test; this may be attributed to the lack of idioms in the curriculum of Departments of English.